Geometry dependence of excitonic couplings and the consequences for configuration‐space sampling. Issue 20 (16th May 2021) - Schieschke, Nils; Bold, Beatrix M.; Dohmen, Philipp M.; Wehl, Daniel; Hoffmann, Marvin; Dreuw, Andreas; Elstner, Marcus; Höfener, Sebastian
Abstract: Excitonic coupling plays a key role for the understanding of excitonic energy transport (EET) in, for example, organic photovoltaics. However, the calculation of realistic systems is often beyond the applicability range of accurate wavefunction methods so that lower‐scaling semi‐empirical methods are used to model EET events. In the present work, the distance and angle dependence of excitonic couplings of dimers of selected organic molecules are evaluated for the semi‐empirical long‐range corrected density functional based tight binding (LC‐DFTB) method and spin opposite scaled second order approximate coupled cluster singles and doubles (SOS‐CC2). While semi‐empirically scaled methods can lead to slightly increased deviations for excitation energies, the excitonic couplings and their dependence on the dimer geometry are reproduced. LC‐DFTB yields a similar accuracy range as density‐functional theory (DFT) employing the ω B97X functional while the computation time is reduced by several orders of magnitude. The dependence of the exchange contributions to the excitonic couplings on the dimer geometry is analyzed assessing the calculation of Coulombic excitonic couplings from monomer local excited states only, which reduces the computational effort significantly. The present work is a necessary first step toward the simulation of excitonic energy transport using semi‐empirical methods. Abstract : Distance and angle dependence of excitonic couplings of selected dimers of organic molecules are assessed using wavefunction‐based and semi‐empirical methods. Geometry‐dependence of exchange contributions to the excitonic couplings are analyzed using Coulomb couplings of monomer excited states. The analysis reveals that exchange effects can be small for certain orientations despite a short intermolecular distance as occurring in molecular crystals.